Low cost Cheque Deposit Box machine - Sainuddin, Mohd Jainal (2006)
This work describes the design of Cheque Deposit Box (CDB). A description of this work covers the hardware and software part, but this work focused in software designing. The CDB is divided into three parts i.e. the input devices, microcontroller, and output devices. Input devices consist of Barcode Reader and switches, while output devices are serial printer, LEDs, and latch. CDB uses Atmel AT89S53 as a microcontroller. The microcontroller is also connected with external memory, I2C EEPROM, and RTC, for clock system. In term of software development, the C Programming Language is used for the microcontroller. Other software such as SDCC, C Compiler, is used for compiling the source code to generate file which microcontroller can understand.